Iron Metabolism as a Potential Mechanism for Inducing TRAIL-Mediated Extrinsic Apoptosis Using Methylsulfonylmethane in Embryonic Cancer Stem Cells - Nipin Sp (MDPI AG, 2021)
Embryonic cancer stem cells (CSCs) can differentiate into any cancer type. Targeting CSC using natural compounds is a good approach as it suppresses cancer recurrence with fewer adverse effects, and methylsulfonylmethane (MSM) is a sulfur-containing compound with well-known anticancer activities. This study determined the mechanistic aspects of the anticancer activity of MSM. We used Western blotting and real-time qPCR for molecular signaling studies and conducted flow cytometry for analyzing the processes in cells. Our results suggested an inhibition in the expression of CSC markers and Wnt/β-catenin signaling. MSM induced TRAIL-mediated extrinsic apoptosis in NCCIT and NTERA-2 cells rather than an intrinsic pathway. Inhibition of iron metabolism-dependent reactive oxygen species (ROS) generation takes part in TRAIL-mediated apoptosis induction by MSM. Suppressing iron metabolism by MSM also regulated p38/p53/ERK signaling and microRNA expressions, such as upregulating miR-130a and downregulating miR-221 and miR-222, which resulted in TRAIL induction and thereby extrinsic pathway of apoptosis. Hence, MSM could be a good candidate for neoadjuvant therapy by targeting CSCs by inhibiting iron metabolism.